BLENDED LEARNING IN SECONDARY EDUCATION: BRIDGING TRADITIONAL AND DIGITAL PEDAGOGIES - Azamova Rukhsora, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: This paper examines the role of blended learning in secondary education, focusing on how the integration of face-to-face instruction and online learning can enhance student engagement, flexibility, and achievement. It explores the theoretical underpinnings of blended learning, outlines its core models, and discusses practical strategies for effective implementation in secondary schools. The paper also addresses challenges such as digital inequality and teacher readiness, offering recommendations for overcoming these barriers.